“THERE ARE NO DISAGREEMENTS AMONG THE MASSES. THERE ARE ON THE TOP...”. DOCUMENTS AND MATERIALS ON THE EXIT OF BALKARIA FROM THE GORSK REPUBLIC AND THE FORMATION OF THE KABARDIN-BALKAR AUTONOMOUS REGION - K. F. DZAMIKHOV; A. G. KAZHAROV; M. S. TAMAZOV (Кавказология, 2021)
An important stage in the formation of the Soviet autonomy of Kabardino-Balkaria is the secession of Balkaria from the Mountain Republic and the solution of the issue of its entry into the united autonomy of the Kabardian and Balkarian peoples. The national self-determination of Balkaria took quite a long period – June 1921 – August 1922. In June 1921, M. Eneev was one of the first statesmen of Kabarda and Balkaria to declare the mistake of creating the Mountain Republic and the need for Balkaria to secede from it. In August 1922, the Regulation on the unification of Kabarda and Balkaria was adopted, which completed the difficult process of agreeing on the mechanisms of unification of Kabarda and Balkaria. During this time, the problem has been discussed at various levels. A large array of archival documents and materials has accumulated, the publication of which will contribute to a deeper study of the creation of the Kabardino-Balkarian Autonomous Region in the early 1920s. Analysis of the documents indicates that attempts to form a separate autonomous region of Balkaria revealed the impossibility of resolving the land issue of the Balkar people at the expense of the territory of Kabarda outside the framework of the general ethnopolitical system. The center, which initiated the unification of Kabarda and Balkaria, pursued an appropriate policy and brought this process to its logical conclusion. At the same time, the historical features of the relationship between Kabardins and Balkars, a long stay in a single administrative-territorial space, the positive experience of administrative and political interaction of elites during the revolution, the Civil War and the post-war period, as well as their national-state preferences were taken into account. There are no documents and materials indicating the unwillingness of the Balkar people to join the united autonomy of Kabarda and Balkaria. Moreover, the decisions of the Constituent Congress of Soviets of the Kabardino-Balkarian Autonomous Region in December 1922 are nothing more than an act of free expression of the will of the Balkar people.